Cytokine Profile at the Beginning of Pregnancy in Mexican Women (Central Asian Journal of Medical Sciences, 2019)
Objectives: To quantify and associate the levels of Th1 pro-inflammatory and Th2 anti-inflammatory cytokines with the anthropometric measurements at the beginning of pregnancy. Methods: This prospective clinical and descriptive study included pregnant women 18 years of age and older. Serum levels of IL-4, IL-6, IL-10, IFN-γ, and TNF-α were measured by ELISA. Correlations were determined among the cytokines and anthropometric variables. Results: From 83 pregnant women IL-4 was significantly higher in Underweight compared to Overweight patients (97.5 ± 3.5 vs. 66.4 ± 17.6 pg/mL, p = .037), Underweight compared to Obesity Class I patients (97.5 ± 3.5 vs. 60.6 ± 17.2 pg/mL, p = .024) and in Normal Weight compared to Obesity Class I patients (72.2 ± 17.7 vs. 60.6 ± 17.2 pg/ mL, p = .026). TNF-α was significantly higher in Normal Weight compared to Obesity Class II patients (41.9 ± 26 vs. 24.9 ± 19.7 pg/mL, p = .031). IL-4 was positively correlated with TNF-α (r2 = .309, p = .005) and negatively correlated with pre-gestational BMI (r2 = -.243, p = .029). IL-10 was positively correlated with IL-4 (r2 = .356, p = .001) and TNF-α (r2 = .308, p = .005). Finally, IFN-γ was negatively correlated with IL-4 (r2 = -.246, p = .025), IL-6 (r2 = -.232, p = .035) and TNF-α (r2 = -.289, p = .008). Conclusion: In Mexican women, there is a low anti-inflammatory cytokine profile at the beginning of pregnancy